INTER-INDIVIDUAL DIFFERENCES IN THE RESPONSES OF VO2MAX TO PHYSICAL ACTIVITY COUNSELLING. Issue 22 (1st November 2016) - Williamson, P; Atkinson, G; Batterham, A
Abstract : Low cardiorespiratory fitness (VO2max ) is an important risk factor for diabetes, cardiovascular disease and some cancers, making lifestyle interventions especially relevant. There is purported to be substantial inter-individual differences in how VO2max responds to lifestyle/exercise interventions. Recently, we described the appropriate approach for quantifying these inter-individual differences. Therefore, we aimed to apply this approach to quantify inter-individual differences in the responses of VO2max . We re-analysed data from the influential 'Activity Counselling Trial' (ACT), which was designed to determine the effects of general lifestyle assistance as well as formal counselling on physical activity and VO2max in 479 men and 395 women. Importantly, an appropriate comparator group was also present in order to quantify 'true' inter-individual differences in VO2max response. For women, the 'true' inter-individual responses in VO2max (expressed as a SD) were found to be±129 (95% Confidence interval: −40 to 187) ml/min in the general lifestyle assistance group and±93 (−91 to 160) ml/min in the formal lifestyle counselling group. For men, true individual differences in response were±116 (95%CI: −130 to 210) ml/min and±148 (−105 to 234) ml/min in the assistance and counselling groups, respectively. Although the mean increase in VO2max was greater in women, this increase corresponded to a trivial effect size. This application of the appropriate analyses to the ACT dataset indicate that, on average, the effects of activity counselling on VO2max were small, although there were moderate 'true' inter-individual differences in the VO2max response in women (0.34 SD) and small 'true' inter-individual differences in men (0.27 SD). Further genotype investigation may therefore be warranted in order to determine the mediators of this observed heterogeneity in response.